Fluctuations of forced vibrations in a medium with resistance - Kovtun, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a differential oscillation equation with coefficients perturbed by Gaussian delta-correlated random processes with a random external force, we obtain closed moment equations. In a special case, the mathematical expectation and the covariance function are found.